2020
DOI: 10.1073/pnas.1917701117
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic effect of thalidomide is independent of teratogenic ubiquitin/proteasome pathway

Abstract: Thalidomide exerts its teratogenic and immunomodulatory effects by binding to cereblon (CRBN) and thereby inhibiting/modifying the CRBN-mediated ubiquitination pathway consisting of the Cullin4-DDB1-ROC1 E3 ligase complex. The mechanism of thalidomide’s classical hypnotic effect remains largely unexplored, however. Here we examined whether CRBN is involved in the hypnotic effect of thalidomide by generating mice harboring a thalidomide-resistant mutant allele of Crbn (Crbn YW/AA knock-in mice). Thalidomide inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…It should be cautioned, however, that, whereas, the anti-inflammatory actions of IMiDs clearly involve cereblon-dependent and -independent mechanisms, so too may pathways that underpin teratogenic, anticancer, and anti-angiogenic actions. Indeed, cereblon-independent anti-angiogenic IMiD actions have been reported [73], and the hypnotic effects of thalidomide likewise appear to be independent of cereblon [150]. Other proteins, in addition to SALL4, such as the tumor protein p63 that has multiple isoforms, the major of which are TAP63 and ∆NP63, are subject to thalidomide-mediated degradation and appear to be involved in different teratogenic phenotypes [151].…”
Section: Discussionmentioning
confidence: 99%
“…It should be cautioned, however, that, whereas, the anti-inflammatory actions of IMiDs clearly involve cereblon-dependent and -independent mechanisms, so too may pathways that underpin teratogenic, anticancer, and anti-angiogenic actions. Indeed, cereblon-independent anti-angiogenic IMiD actions have been reported [73], and the hypnotic effects of thalidomide likewise appear to be independent of cereblon [150]. Other proteins, in addition to SALL4, such as the tumor protein p63 that has multiple isoforms, the major of which are TAP63 and ∆NP63, are subject to thalidomide-mediated degradation and appear to be involved in different teratogenic phenotypes [151].…”
Section: Discussionmentioning
confidence: 99%
“…53 Concordantly, the (S)-enantiomer exhibits about 10-fold stronger binding to CRBN, 54 whereas the hypnotic effect of thalidomide is reportedly CRBN-independent. 55 Recent findings have improved our understanding of the molecular mechanisms of thalidomide embryopathy. In 2018, two independent groups reported Spalt-like transcription factor 4 (SALL4) as a neosubstrate involved in the teratogenicity of thalidomide.…”
Section: Teratogenic Effectsmentioning
confidence: 99%
“…53 Concordantly, the ( S )-enantiomer exhibits about 10-fold stronger binding to CRBN, 54 whereas the hypnotic effect of thalidomide is reportedly CRBN-independent. 55…”
Section: Molecular Mechanisms Of Action Of Thalidomide and Its Deriva...mentioning
confidence: 99%
“…Very few studies have explored the function of SON in sleep-wakefulness regulation; however, the number of damaged cells was increased in the SON after severe sleep deprivation [ 43 ]. Recently, it was reported that the hypnotic effect of thalidomide, a nonbarbiturate hypnotic agent, may be associated with the activation of vasopressin-containing neurons in SON due to the significantly increased c-fos expression [ 45 ]. Interestingly, a recent study reported that SON neurons are commonly activated by various classes of general anesthetics, including isoflurane (1%-1.2%), propofol (180 mg/kg), ketamine (100 mg/kg), and dexmedetomidine (100 μg/kg) determined by increased c-fos expression, recording of brain slices, and in vivo recording of multichannel electrophysiology [ 18 ].…”
Section: Induction Of Unconsciousness By General Anestheticsmentioning
confidence: 99%